Psychological predictors of injury among professional soccer players - Devantier, C. (Sport Science Review, 2011)
Numerous empirical studies suggest that specific psychological factors influence the frequency and severity of sport injuries. The main purpose of the present study is to outline the psychological factors, which predict increased injury vulnerability among professional male soccer players in Denmark. Based on the Stress-Injury Model by Williams & Anderson (1998) it is hypothesized that low coping resources, high competitive trait anxiety, and history of previous injuries would be positively related to an increased risk of injury occurrence and severity. Methods: The soccer players (N = 87) were asked to report history of previous injuries within the last 12 months. Furthermore, 2 questionnaires were used; Competitive Trait Anxiety Test, and Athletic Coping Skills Inventory - 28 (ACSI-28). Injuries were prospectively recorded throughout a period of approximately 3 months by the team's medical staff (doctors and physiotherapists). Results: Study findings clearly suggest that history of previous injury and coping with adversity are the best predictors of injury occurrence. These factors explained between 7 % and 11 % of the total variance of injury occurrence and days lost due to injury respectively. Furthermore, the same variables were found very successful in prediction injury occurrence. Conclusions: The findings support the suggestions that psychological factors can be utilized as a predictive measurement to sport injuries, which should be considered by coaches and medical staff in order to reduce vulnerability to injury.